Changes in the Religion of the Nepalese of Manipur: Conversion and Acculturation - Bachaspatimayum, Mary (Bodhi: An Interdisciplinary Journal, 2013)
Bodhi: An Interdisciplinary Journal, 5, 2011, Page 34-52 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8044